Non-Linear Effects of Political Connections on Corporate Investment and the Moderating Role of Cash Holdings in Indonesian SOEs - Wicaksari, Erisa Aprilia; Rini Setyo Witiastuti; Kris Brantas Abiprayu; Nabila Rifa Hanifah (Universitas Negeri Semarang, 2024)
This study investigates the complex relationship between political connections and corporate investment, focusing on state-owned enterprises (SOEs) in Indonesia during the period 2018–2021. Drawing on agency theory and political economy frameworks, the research proposes a non-linear (inverted U-shaped) effect of political ties on firm-level investment decisions. Furthermore, the study examines the moderating role of cash holdings, positing that financial slack amplifies both the benefits and drawbacks of political affiliations. Using panel regression models with fixed effects, the analysis reveals a significant inverted U-shaped relationship between political connection intensity and investment levels, confirming the hypothesized non-linearity. Additionally, interaction terms show that cash holdings strengthen this non-linear pattern: firms with higher cash reserves are more sensitive to both the enabling and distortionary effects of political connections. These findings are robust to alternative specifications and contribute to the understanding of political capital’s nuanced role in corporate finance, especially within hybrid political-economic systems like Indonesia’s. The results suggest that while political connections may serve as strategic assets under certain conditions, they can also generate inefficiencies when unchecked.